(untitled) (Revista Educação, Artes e Inclusão, 2023)
Academic and scientific productions are increasingly multimodal with the popularization of graphic production and image editing software. However, these images need to be accessible for people with some limitation in reading this type of resource. And one of the resources to make these images accessible is audio description. This study aims to analyze the multimodal arrangement of images that are part of academic productions that were directed to be made accessible through audio description. The focus is to verify how the constituent elements of the images were arranged in the visual space and how this is reflected in the audio description script. Based on the assumptions of Social Semiotics and Multimodality (Ribeiro, 2016, 2018; Gualberto e Pimenta, 2019) and Intersemiotic Translation (Plaza, 2003), the composition function of the Visual Design Grammar - GDV - by Kress and Van Leeuwen (2006); and the principles of audio description by Lima (2011). Ten images classified into categories based on ABNT standards for academic work were selected. The theoretical-empirical evaluation raised questions and possibilities in the work of creating and producing these images. By knowing the translational process of audio description, it is possible to better think about the multimodal arrangement of elements for the composition of more accessible images.